Polyphony and politics: Representing and translating culture, race and gender in Puccini’s Turandot - Benang Xuan (JoSTrans: The Journal of Specialised Translation)
In the context of a more radical and critical climate of opera performance and audience response, this article investigates the representation and performance of Chinese-related images, characters and themes in various productions of Puccini’s Turandot, mainly those by Franco Zeffirelli, Zhang Yimou, Chen Kaige, Chen Xinyi and Robert Wilson, with particular reference to their English and/or Chinese surtitles. It argues that, while the impression of contrived harmony in Puccini’s mythologising of ancient China through yellowface performance is inevitably undermined by its contemporary cultural-political ramifications, the creative indeterminacy of the translational discourse can help to recover in this exquisite work the diversity and relevance that we deem necessary in our present time. Meanwhile, although cultural, racial and gender differences should be properly understood and duly respected in operatic contexts, it is imperative that representational and translational choices not be decided or evaluated by those considerations alone, that they not polarise into two warring ideological positions, i.e., Occidental versus Oriental, white versus non-white, male versus female.